KAJIAN IDEOLOGI PURA BUKIT INDRAKILA DI DESA DAUSA KECAMATAN KINTAMANI KABUPATEN BANGLI (PERSPEKTIF ETNOPEDAGOGI) - Gede Septiwima; Ni Luh Gede Hadriani; I Wayan Gata (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This study aims to answer: (1) What is the shape of the building and the Most Gih in Pura Bukit Indrakila Based on Oral Tradition?, (2) What is the Function of Pura Bukit Indrakila, and (3) How to Instill Ideology Through an Ethnopedagogical Approach to the Young Generation of Hindu Temples Indrakila Hill in Dausa Traditional Village, Kintamani District, Bangli Regency? To answer the above problems, several theories are used, namely (1) Theory of Form (Nature as Exsemplar in Architeture) Soekmono, (1974), Joseph Rykwert 1991, Luddwigh Witgenstein, 1973), Giovani Pietro, 1672), (2) Ideological Theory Althusser, (2006) and (3) Ethnopedagogical Theory Hafid, et al (2015), (Priadi Surya, 2011), (Tilaar. 2015), Bernstein (2004) This study uses a phenomenological approach. With interview data collection techniques, Document Study., and Participation Observation (Participant Observation). Triangulation and qualitative descriptive analysis. The results of the research on instilling ideology for the younger generation of Hindus are bright ideas that have been designed by the traditional and religious elders in the seka teruna teruni/deha teruna forum already have a vision and way of looking ahead as a comprehensive, as a way of looking at all things. something in general (see Ideology in everyday life) and some philosophical directions, or a group of ideas proposed by traditional and religious leaders to the younger generation of Hindus in particular and social groups of community members who are members of gebog satak in general as the proponents of Pura Bukit Indrakila in Dausa Village. The main purpose behind the planting of ideology is to offer change through a normative thought process, in this case the religious leaders and traditional leaders have fully designed the direction and goals to be achieved in terms of planting this ideology.Keywords: Ethnopedagogical, Pura Bukit Indrakila